Effects of papaya leaves crude extract on the physicochemical and sensory characteristics of marinated chicken meat / Normah Ismail and Rosliana Rosman - Ismail, Normah; Rosman, Rosliana (Universiti Teknologi MARA Shah Alam, 2018)
The purpose of this study was to investigate the effect of papaya leaves crude extract on the physicochemical properties of marinated chicken meat. Papaya leaves was extracted with sodium acetate (CH3COONa) buffer (pH 7.2) at room temperature. Protein concentration and activity of enzyme in the crude extract were determined by using UVSpectrophotometer. The crude extract was mixed with marinated ingredients and then coated onto chicken meat which was subsequently kept for overnight in refrigerator at chill temperature. Protein concentration of the enzyme was identified as 166.36 μg/μl and enzyme activity was 1.28 CDU/ml. Results also showed that lightness (L*), cooking loss and shrinkage of the marinated chicken were higher than control. Redness (a*), yellowness (b*), protein content, water-holding capacity, shear force, and texture profile analysis were lower than control. Microstructure analysis showed that the chicken meat muscle was destructed in the presence of papaya crude extract. Sensory acceptability evaluation of marinated chicken which was carried out by using 9 point hedonic scale suggested that chicken meat treated with papaya crude extract gave significant effect on texture, juiciness, flavour and overall acceptability compared to commercial bromelain. Additionally, the use of papaya crude extract gave a significant effect on the physicochemical properties of marinated chicken.